PENGARUH TINGKAT KETERBACAAN MATERI PELAJARAN BAHASA INDONESIA TERHADAP HASIL BELAJAR SISWA KELAS XI IPS MAN MALAKAJI GOWA - Adelia, Adelia; Muin, Nurmiah; Puspitasari, Andi (LPPM Institut Pendidikan Nusantara Global, 2023)
Thesis Department of Indonesian Language and Literature Education, Faculty of Sastra, Indonesian Muslim University. Supervised by Dr. Hj. Nurmiah Muin, SE., M.Pd, as supervisor I and Andi Puspitasari, S.Pd., M.Pd, as supervisor II. This study aims to determine and analyze the effect of the readability level of Indonesian subject matter on student learning outcomes in class XI IPS 3 MAN Malakaji Gowa. This study uses ex post facto with a comparative causal research type. The population used in this study consisted of students of class XI IPS 3 MAN Malakaji Gowa while the sample was 28 students of class XI IPS 3 MAN Malakaji Gowa. Data collection techniques are observation sheets, tests, interviews, and documents. The research instrument uses documentation and interviews. The data analysis technique used the linca regression analysis technique. The results of the study can be concluded that the learning outcomes of the 28 students who were obtained during the learning process were 6 students whose grades did not reach the KKM score, while those who obtained moderate scores were 4 students and while those who received high scores were 14 students. So it can be concluded that the level of legibility of the subject matter has an effect on student learning outcomes. Based on the results of the t-test, the sig value is 0.0035 > 0.05 while the t-value is -0.982 <2.055 the t-table value, meaning that X has no effect on Y, it can be concluded that the hypothesis is rejected or the level of readability of Indonesian subject matter has no effect on the results student learning.